(untitled) (Global Journal of Management and Business Research, 2018)
Nowadays Bangladeshi Multinational Companies are actively engaged in Corporate Social Responsibility. However, most of the activities are confined to earn publicity and positive political image only. External Corporate Social Activities are very popular in the corporate world. An unholy competition is prevailing among the giant Multinational companies to show off their activities. Business conglomerates do not pay much attention for the workers after retirement benefit. This study was conducted to measure the impact of Corporate Social Responsibility on the reduction of workers vulnerability after retirement for Bangladeshi Garment Industries. A total of 98 usable questionnaires gathered from 11 Multinational Companies (MNC) in Bangladesh. Outcomes of correlation analysis show that there is a statistically significant relationship between internal Corporate Social Responsibilities and protected retired life of Garments workers. Findings also suggest that when MNCs takes interest and carry out social responsibility than it enhances high productivity, greater teamwork, and high organizational commitment.